2019
DOI: 10.1111/1745-9133.12412
|View full text |Cite
|
Sign up to set email alerts
|

Research on body‐worn cameras

Abstract: Research Summary In this article, we provide the most comprehensive narrative review to date of the research evidence base for body‐worn cameras (BWCs). Seventy empirical studies of BWCs were examined covering the impact of cameras on officer behavior, officer perceptions, citizen behavior, citizen perceptions, police investigations, and police organizations. Although officers and citizens are generally supportive of BWC use, BWCs have not had statistically significant or consistent effects on most measures of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
175
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 265 publications
(196 citation statements)
references
References 79 publications
1
175
0
Order By: Relevance
“…Fortunately, researchers have become very interested in studying BWCs in the latter half of the 2010s. For example, by November 2015, Lum et al's (2015) review of both completed and in‐progress studies for the Laura and John Arnold Foundation found that completed studies about BWCs had grown to more than a dozen, with 30+ additional studies underway. Later, Cubitt, Lesic, Myers, and Corry (2017) reviewed 11 articles on the impacts of BWCs.…”
Section: Introductionmentioning
confidence: 99%
“…Fortunately, researchers have become very interested in studying BWCs in the latter half of the 2010s. For example, by November 2015, Lum et al's (2015) review of both completed and in‐progress studies for the Laura and John Arnold Foundation found that completed studies about BWCs had grown to more than a dozen, with 30+ additional studies underway. Later, Cubitt, Lesic, Myers, and Corry (2017) reviewed 11 articles on the impacts of BWCs.…”
Section: Introductionmentioning
confidence: 99%
“…There has been extensive uptake of body-worn video (BWV) cameras by Australian, UK, and US law enforcement agencies in the absence of clear evidence demonstrating camera efficacy (Lum et al 2019). This paper reports the findings of a 6-month randomized controlled trial of BWV undertaken by the Western Australia Police Force (WAPF) in 2016.…”
Section: Introductionmentioning
confidence: 99%
“…Police officers (Jennings et al, 2014;Lum, Stoltz, Koper, & Scherer, 2019) and members of the public (ODS Consulting, 2011;White et al, 2017) have both been shown to support police use of BWCs, but more research is needed to develop evidence-based understandings of the effects of this technology on perceptions of police and reactions to police. Research that manipulates police use of BWCs (i.e., intentionally varies whether a BWC is used or not) and documents public perceptions following a police interaction is particularly important in this regard.…”
mentioning
confidence: 99%